Biofortification with selenium and lithium improves nutraceutical properties of major winery grapes in the Midwestern United States. (1st September 2020) - Zhao, Hefei; Xie, Xiaoqing; Read, Paul; Loseke, Benjamin; Gamet, Stephen; Li, Wenkuan; Xu, Changmou
Summary: Enriching the micronutrients, selenium (Se) and lithium (Li), in grapes to improve their nutraceutical properties were implemented by foliar application of organic fertiliser rich in Se and Li onto five grape cultivars. The effects of this biofortification on vine vigour, fruit quality, overall micronutrients and phenolic compounds also were investigated. Agronomic biofortification was found greatly increased the Se and Li content in the whole grape by multiple times, meanwhile it did not significantly affect the vine vigour and fruit quality of grapes. However, the biofortification did impact the Ionome (including all the mineral nutrients and trace elements) and phenolic compounds in grapes and this varied among cultivars. This study demonstrated foliar spray of organic Se/Li fertiliser was a very effective strategy to biofortify these micronutrients in grape berries, particularly in the skin, and therefore might be a promising strategy to increase the consumption and awareness of these grapes. Abstract : Grapes in the Midwestern U.S. were very low in selenium and lithium contents. Foliar spray of Se and Li fertilizers was effective to biofortify these micronutrients, which did not significantly affect the growth and fruit quality of grapes.